2020
DOI: 10.1186/s12903-020-01296-z
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine penetrates through gingival sulcus unlike keratinized gingiva and evokes remote vasoconstriction in human

Abstract: Background It has been demonstrated in non-oral tissues that the locally evoked vasoconstriction could elicit remote vasoconstriction. This study aimed to investigate the spreading vasoconstrictor effects of epinephrine in the gingiva. Methods Gingival blood flow (GBF) was measured by laser speckle contrast imager in 21 healthy volunteers. In group A, two wells were fabricated from orthodontic elastic ligature and placed 2 mm apicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Better blood flow recovery may facilitate wound healing in males. In previous investigations [ 5 , 51 , 52 ], blood flow changes induced either by nitric oxide, epinephrine, or surgery were not correlated with the gingival thickness measured by the ultrasonic instrument. Therefore, gender differences cannot be explained by biotype.…”
Section: Discussionmentioning
confidence: 86%
“…Better blood flow recovery may facilitate wound healing in males. In previous investigations [ 5 , 51 , 52 ], blood flow changes induced either by nitric oxide, epinephrine, or surgery were not correlated with the gingival thickness measured by the ultrasonic instrument. Therefore, gender differences cannot be explained by biotype.…”
Section: Discussionmentioning
confidence: 86%
“…Physiologically, the Water Temperature (WT) 20 o C method with the addition of 0.25 and 0.50 l/s Water Speeds causes local arteriolar and venular vasoconstriction. This vasoconstriction is caused by reflex action of smooth muscle arising from stimulation of the autonomic nervous system and the release of epinephrine and norepinephrine [17]. However, if the cold continues to be given for 15 to 30 minutes there will be a vasodilation phase that occurs intermittently for 4 to 6 minutes.…”
Section: Multivariate Test Resultsmentioning
confidence: 99%
“…This is in line with similar studies on the effects of epinephrine in humans. Vag et al 25 studied gingival blood flow with LSCI in human healthy volunteers and found a 50 % decrease after the administration of 2.24 μg epinephrine. Ghali et al 21 and O’Malley et al studied the effect of epinephrine in the head and neck, where perfusion was found to decrease to approximately 56% (10 μg/ml) and 25–50% (5–10 μg/ml) 22 of the initial value.…”
Section: Discussionmentioning
confidence: 99%